2008
DOI: 10.1111/j.1443-9573.2007.00319.x
|View full text |Cite
|
Sign up to set email alerts
|

Human embryonic stem cells and liver diseases: From basic research to future clinical application

Abstract: Human embryonic stem cells (hESC) provide access to the earliest stages of human development and because of their high proliferation capability, pluripotency and low immunogenicity may serve as a potential source of specialized cells for regenerative medicine. hESC-derived hepatocyte-like cells exhibit characteristic hepatocyte morphology, express hepatocyte markers and are capable of executing a range of hepatocyte functions. However, there are many challenges and obstacles to be overcome before the use of hE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Since the first successful attempts on bone marrow transplant for treating leukemia [3], a number of similar trials were initiated for treating several other diseases [48]. After a few decades from its first demonstration of successful clinical trials, stem cells treatments now hold a promising impact to treat various degenerative and genetic diseases including certain type of cancers [9,10], neurological diseases [11], autoimmune diseases [12] restoration of sight [13], wound healing [14], cardiac diseases [15], liver diseases [16], metabolic disorders [17], spinal cord injury [18] and bone disorders [19,20]. Thus, stem cell therapy has received stunning applause from the majority of the world population, in a hope that is expected to cater the need for diseases treatment and personalized medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first successful attempts on bone marrow transplant for treating leukemia [3], a number of similar trials were initiated for treating several other diseases [48]. After a few decades from its first demonstration of successful clinical trials, stem cells treatments now hold a promising impact to treat various degenerative and genetic diseases including certain type of cancers [9,10], neurological diseases [11], autoimmune diseases [12] restoration of sight [13], wound healing [14], cardiac diseases [15], liver diseases [16], metabolic disorders [17], spinal cord injury [18] and bone disorders [19,20]. Thus, stem cell therapy has received stunning applause from the majority of the world population, in a hope that is expected to cater the need for diseases treatment and personalized medicine.…”
Section: Introductionmentioning
confidence: 99%
“…If the ESC-derived hepatocytes are to be transplanted in vivo, they offer the Liver International (2012) advantage of unlimited supply, well-defined characteristics/traits that are driven by specific in vitro differentiation conditions and confidence in biosafety (39). Although these advantages are met in many differentiation protocols (8)(9)(10)(11)(40)(41)(42)(43) including ours, the issue of certainty that the transplanted cells indeed function as hepatocytes still remains. Our protocol defines the sum of parameters useful for functional monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Before cell transplantation for treating liver disease, cells should fulfill numerous criteria, including safety, reproducibility, xeno-free, and long-term function (Table 3 ). ES-derived cells are allogeneic and, therefore immunogenic, increasing the risk for allograft rejection and necessitating immunosuppression [ 105 ]. It has been shown that HLCs led to a tumor after transplantation.…”
Section: Potential Cell Sources To Treat Liver Diseasementioning
confidence: 99%